Inhibition of Glycogen Synthase Kinase 3β Activity in the Basolateral Amygdala Disrupts Reconsolidation and Attenuates Heroin Relapse - Xie, Yuanyang; Zhang, Yingfan; Hu, Ting; Zhao, Zijin; Liu, Qing; Li, Haoyu (Frontiers in Molecular Neuroscience, 2022)
Exposure to a heroin-associated conditioned stimulus can reactivate drug reward memory, trigger drug cravings, and induce relapse in heroin addicts. The amygdala, a brain region related to emotions and motivation, is involved in processing rewarding stimulus. Recent evidence demonstrated that disrupting the reconsolidation of the heroin drug memories attenuated heroin seeking which was associated with the basolateral amygdala (BLA). Meanwhile, neural functions associated with learning and memory, like synaptic plasticity, are regulated by glycogen synthase kinase 3 beta (GSK-3β). In addition, GSK-3β regulated memory processes, like retrieval and reconsolidation of cocaine-induced memory. Here, we used a heroin intravenous self-administration (SA) paradigm to illustrate the potential role of GSK-3β in the reconsolidation of drug memory. Therefore, we used SB216763 as a selective inhibitor of GSK-3β. We found that injecting the selective inhibitor SB216763 into the BLA, but not the central amygdala (CeA), immediately after heroin-induced memory retrieval disrupted reconsolidation of heroin drug memory and significantly attenuated heroin-seeking behavior in subsequent drug-primed reinstatement, suggesting that GSK-3β is critical for reconsolidation of heroin drug memories and inhibiting the activity of GSK-3β in BLA disrupted heroin drug memory and reduced relapse. However, no retrieval or 6 h after retrieval, administration of SB216763 into the BLA did not alter heroin-seeking behavior in subsequent heroin-primed reinstatement, suggesting that GSK-3β activity is retrieval-dependent and time-specific. More importantly, a long-term effect of SB216763 treatment was observed in a detectable decrease in heroin-seeking behavior, which lasted at least 28 days. All in all, this present study demonstrates that the activity of GSK-3β in BLA is required for reconsolidation of heroin drug memory, and inhibiting GSK-3β activity of BLA disrupts reconsolidation and attenuates heroin relapse.